PENGARUH KARAKTERISTIK PASIEN TERHADAP POLA PERESEPAN OBAT ANTIHIPERTENSI DI PUSKESMAS DEKET KABUPATEN LAMONGAN - Muhammad Syariful Imam; Zaenal Fanani (Yayasan Nusantara Hasana Berdikari, 2026)
Hypertension is a non-communicable disease with a continuously increasing prevalence and contributes significantly to the incidence of cardiovascular disease. In service practice, antihypertensive drug prescribing patterns still show variations influenced by age, gender, and comorbidities. This study aims to analyze the influence of patient characteristics on antihypertensive drug prescribing patterns at the Deket Community Health Center in Lamongan Regency. This study used a retrospective and cross-sectional design. Research data were obtained from prescriptions and medical records of hypertensive patients for the period November 2025. The study population included all prescriptions containing antihypertensive drugs, with a sample of 85 prescriptions taken using a simple random sampling technique. Independent variables included age, gender, and comorbidities, while the dependent variable was the antihypertensive drug prescribing pattern. Data analysis was performed descriptively and analytically using appropriate statistical tests. The results of the study at the Deket Community Health Center, Lamongan Regency, the most were women at 76% (65 patients), the most aged ≥60 at 54.12% (46 patients), with comorbidities of diabetes mellitus at 55.29% (47 respondents). The description of the accuracy of antihypertensive prescription patterns at the Deket Community Health Center, Lamongan Regency based on the correct indication was 100%, the correct patient was 92.94% of cases, the correct drug reached 95.29%, the correct dose was 65 prescriptions (76.47%) and the correct method of use was 70.59%. There is a significant relationship between gender and prescribing patterns with a significance value of 0.013 <0.05 with an odds ratio of 0.252, there is no significant relationship between age and prescribing patterns with a significance value of 0.235>0.05 and an odds ratio of 1.682 and there is a significant relationship between comorbidities and prescribing patterns with a significance value of 0.019 <0.05 and a fairly large odds ratio value between the two characteristics, namely 3.000.